2018
DOI: 10.1016/j.pharep.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion attenuates morphine tolerance and dependence: Possible role of glutamate, norepinephrine, inflammation, and oxidative stress

Abstract: Bupropion efficacy in attenuation of morphine tolerance and dependence with its high safety and tolerability profile provide an alternative option to conventional agents e.g., ketamine and clonidine to modulate these phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…34 Cerebral oxidative stress has been well described during acute opioid withdrawal. [14][15][16] Using in vivo MRS, we were able to demonstrate a significant decrease in [GSH] at 120 min after naloxone, compared with pre-withdrawal scans within the salinetreated group, and a significantly lower [GSH] at 120 min after naloxone in OD rats treated with saline vs NAC. Pre-withdrawal GSH concentrations were not significantly different between groups.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…34 Cerebral oxidative stress has been well described during acute opioid withdrawal. [14][15][16] Using in vivo MRS, we were able to demonstrate a significant decrease in [GSH] at 120 min after naloxone, compared with pre-withdrawal scans within the salinetreated group, and a significantly lower [GSH] at 120 min after naloxone in OD rats treated with saline vs NAC. Pre-withdrawal GSH concentrations were not significantly different between groups.…”
Section: Discussionmentioning
confidence: 87%
“…In an adult opioid-dependent animal model, other investigators have determined that withdrawal precipitates oxidative stress, and measures of oxidative stress directly relate to withdrawal behaviors, which are responsive to antioxidants. [14][15][16] In addition to oxidative stress, there is a disruption of glutamate homeostasis during opioid withdrawal resulting in an increase in synaptic glutamate (excitatory neurotransmitter) that leads to increased neuronal firing. [17][18][19][20][21] This increase in synaptic glutamate occurs because of decreased tone and function of the extrasynaptic metabotropic glutamate autoreceptors, mGluR2/3, which normally inhibits synaptic glutamate release (this decreased inhibition leads to increased synaptic glutamate) 17,20 and decreased function of glial glutamate transporter-1, which causes reduced glutamate elimination from extracellular space resulting in spillover of synaptic glutamate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 On the other hand, many studies indicated the involvement of the glutamatergic system in tolerance and dependence on opioids. [35][36][37] Some researchers have also showed that the pro-inflammatory cytokines, especially TNF-α through NF-κB inhibits the expression of Glutamate Carriers (GCs), especially the Glutamate-Aspartate (GLAST) vector, leading to increased neurotoxicity due to increases in synaptic glutamate levels. TNF-α promotes the expression of AMPA receptors in the CNS and also influences the activity of the glutamatergic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of these receptors increases dopamine release in the prefrontal cortex and induces feelings of euphoria in the user. 13 However, morphine can induce oxidative stress in organs such as the brain., 14 increase oxidative stress and neuronal apoptosis, destroy DNA, and produce reactive oxygen species. [14][15][16] Among the brain areas heavily affected by morphine is mesocorticolimbic and brain's prefrontal regions.…”
Section: Introductionmentioning
confidence: 99%